Discourse of Faking by Civil Servant Selection Participants on YouTube - Yusuf Hadi Yudha; Rustono Farady Marta; Hana Panggabean (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
Technological advances and rapid development of the internet, has pushed YouTube to become one of the new communication media by communicating information through audio and video. This information affects the personality of individuals who have a specific purpose in their efforts to communicate. With YouTube, anyone can freely watch whatever information is presented, and create various content without any permits or censors. This condition made some of content creators leaking a number of psychological tests that should be confidential, by making discussions, as well as tips and tricks on how to get a high score on these tests. This study aims to show how a civil servant candidate openly communicates to the public by creating video content on YouTube about tips and tricks for giving deceptive responses (faking) on the Personal Characteristics Test (TKP) used in civil servant selection test (CPNS) in order to get high score in this test. Analysis of the video using Critical Discourse Analysis from Theo van Leeuwen found that, in order to surpass the predetermined TKP passing grade, test takers were required to play the role of being an ideal figure of a civil servant. As in CPNS selection context, the video also reveals that by faking the test answer, it can increase the chances of participants to get high scores in the test. The self-reporting test format, also helped test takers easily fake the test by selecting answers according to the ideal profile of a civil servant, not answering according to his true state, as is expected in psychological tests in general. Kemajuan teknologi dan berkembang pesatnya penggunaan internet, mendorong YouTube menjadi salah satu bentuk media komunikasi baru untuk menyampaikan informasi melalui tayangan-tayangan berupa audio dan video. Informasi tersebut mempengaruhi kepribadian individu yang memiliki tujuan tertentu dalam upayanya berkomunikasi.Pada kanalYouTube, siapapun dapat dengan bebas menonton dan mengakses informasi apa saja yang disajikan, serta berkreasi membuat berbagai konten tanpa ada batasan perizinan ataupun sensor. Hal ini membuat sejumlah pembuat konten yang tidak bertanggung jawab membocorkan sejumlah tes psikologi yang seharusnya rahasia, dengan membuat pembahasan, serta tips dan trik bagaimana mendapatkan skor tinggi dalam tes tersebut. Penelitian ini bertujuan untuk mengetahui bagaimana peserta seleksi Calon Pegawai Negeri Sipil (CPNS) dan pemberian respon pengelabuan pada pengerjaan Tes Karakteristik Pribadi (TKP) ditampilkan dalam diskursus, khususnya dalam video YouTube berjudul “TIPS DAN TRIK MENJAWAB SOAL TKP CPNS 2019”.Analisis terhadap video menggunakanAnalisis Wacana Kritisdari Theo van Leeuwen menemukan bahwa, agar dapat melampaui passing grade yang telah ditetapkan,peserta tes dituntut berperan menjadi sosok ideal seorang PNS. Dalam konteks seleksi CPNS, video tersebut mengungkapkan pula bahwa dengan melakukan pengelabuan,dapat meningkatkan peluang untuk mendapatkan skor tinggi dalam tes tersebut. Desain tes yang berupa pelaporan diri, turut membuat peserta tes dapat dengan mudah melakukan faking dengan memberikan jawaban sesuai profil ideal seorang PNS, dan bukan menjawab sesuai dengan keadaan dirinya yang sebenarnya, sebagaimana layaknya yang diharapkan dalam tes psikologi pada umumnya.